Understanding drivers of human tolerance towards mammals in a mixed-use transfrontier conservation area in southern Africa. (February 2021) - Kansky, Ruth; Kidd, Martin; Fischer, Joern
Abstract: Living with wild mammals is a critical challenge globally, especially in mixed-use landscapes such as Transfrontier Conservation Areas that aim to conserve wildlife as well as implement programs to improve livelihoods. The success of such initiatives depends on local communities willingness to tolerate potential costs from wildlife. However, the drivers of tolerance in such landscapes are not well understood, especially the relative importance of non-monetary costs and benefits, which are often not measured in surveys. We conducted surveys based on the Wildlife Tolerance Model (WTM) to investigate the drivers of tolerance for 286 farmers from 78 villages living around Sioma-Ngewzi National Park in southern Zambia, a section of the Kavango-Zambezi Transfrontier Conservation Area (KAZA), where monetary benefits from wildlife are not available. We found that non-monetary benefits were significant drivers of tolerance, meaning that in the absence of monetary benefits, non-monetary benefits can promote tolerance. Next, we compared drivers of tolerance across five large mammal species and found some similarities in drivers that will allow development of common strategies to promote tolerance for all five species in the landscape. These were increasing non-monetary benefits, reducing the non-monetary costs from all wildlife, increasing empathy towards wildlife, and improving relationships with Zambian Wildlife Authority.